2021
DOI: 10.1039/d0fo03294h
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanobilin is the molecule responsible for the nephroprotective action of phycocyanin in acute kidney injury caused by mercury

Abstract: C-phycocyanin (CPC) exerts therapeutic, antioxidant, anti-inflammatory and immunomodulatory actions. It prevents oxidative stress and acute kidney damage caused by HgCl2. However, the exact mechanism of the pharmacological action of C-phycocyanin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…(2021) demonstrated that PCB is responsible for antioxidant nephroprotection by phycocyanin in the HgCl 2 -induced kidney injury in mice. 7 Therefore, PCB might be an essential material basis for phycocyanin's nutraceutical functions.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) demonstrated that PCB is responsible for antioxidant nephroprotection by phycocyanin in the HgCl 2 -induced kidney injury in mice. 7 Therefore, PCB might be an essential material basis for phycocyanin's nutraceutical functions.…”
Section: Introductionmentioning
confidence: 99%
“…C-PE may act as a prodrug that leads to the release of the phycoerythrobilin moiety into the gastrointestinal tract, as previously demonstrated by our group for C-PC and phycocyanobilin [22]. C-PC is known to break down into chromo-peptides that contain phycocyanobilin, followed by the apparent absorption of linear tetrapyrrole compounds facilitated by the action of intestinal peptidases [24,25].…”
Section: Discussionmentioning
confidence: 55%
“…In recent years, the use of nutraceuticals from cyanobacteria and their metabolites has proven effective against renal damage (e.g., AKI) stemming from toxicants or chronic kidney disease [16,[20][21][22]. Purified C-PE presently demonstrated nephroprotective activity when tested against HgCl 2 -induced AKI, as evidenced by the reduction found in oxidative stress and ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations